2022
DOI: 10.3390/ijms232416177
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Dependent Interplay of Lithium and Tricyclic Antidepressants, Amitriptyline and Desipramine, on N-methyl-D-aspartate Receptors

Abstract: The facilitated activity of N-methyl-D-aspartate receptors (NMDARs) in the central and peripheral nervous systems promotes neuropathic pain. Amitriptyline (ATL) and desipramine (DES) are tricyclic antidepressants (TCAs) whose anti-NMDAR properties contribute to their analgetic effects. At therapeutic concentrations <1 µM, these medicines inhibit NMDARs by enhancing their calcium-dependent desensitization (CDD). Li+, which suppresses the sodium–calcium exchanger (NCX) and enhances NMDAR CDD, also exhibits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…There is evidence that lithium, by inactivating the Src kinase, inhibits the phosphorylation of NR2B, a subunit of the NMDA receptor, which leads to its inactivation [ 29 , 30 ] and inhibits NMDA receptor expression in rats [ 31 ]. In addition, it has been shown that Li + inhibits the sodium–calcium exchanger, increasing intracellular Ca 2+ levels, and enhances calcium-dependent desensitization of the NMDA receptor [ 32 , 33 ]. In the study [ 24 ], it was found that short-term (1 h) treatment of cultures with lithium did not affect glutamate-induced Ca 2+ entry into neurons, while long-term treatment (7 days) significantly reduced glutamate-induced Ca 2+ entry into neurons.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that lithium, by inactivating the Src kinase, inhibits the phosphorylation of NR2B, a subunit of the NMDA receptor, which leads to its inactivation [ 29 , 30 ] and inhibits NMDA receptor expression in rats [ 31 ]. In addition, it has been shown that Li + inhibits the sodium–calcium exchanger, increasing intracellular Ca 2+ levels, and enhances calcium-dependent desensitization of the NMDA receptor [ 32 , 33 ]. In the study [ 24 ], it was found that short-term (1 h) treatment of cultures with lithium did not affect glutamate-induced Ca 2+ entry into neurons, while long-term treatment (7 days) significantly reduced glutamate-induced Ca 2+ entry into neurons.…”
Section: Discussionmentioning
confidence: 99%
“…This enhanced effect of PCLLA-nanoHA may be attributed to its increased degradability, leading to the release and exposure of HA components, such as calcium and phosphate ions [39,40], which are known to activate downstream signaling pathways, including the JAK-STAT, PI3K-Akt pathways, and mitochondrial pathways [41,42]. However, further investigation is needed to elucidate the specific mechanisms by which ions directly regulate macrophages function and how leptin protein responds to ions, ultimately influencing macrophages fate.…”
Section: Discussionmentioning
confidence: 99%